2017
DOI: 10.1371/journal.pone.0184482
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, health protection, and sexual practices among young men who have sex with men: Using social action theory to guide HIV prevention efforts

Abstract: The present study addresses gaps in the literature related to theory development for young men who have sex with men (YMSM) sexual practices through the application and modification of Social Action Theory. Data come from the Healthy Young Men study (N = 526), which longitudinally tracked a diverse cohort of YMSM ages 18–24 to characterize risk and protective factors associated with drug use and sexual practices. Structural equation modeling examined the applicability of, and any necessary modifications to a Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(77 reference statements)
0
4
1
Order By: Relevance
“…In contrast to our findings, it was recently observed that MSM in England self-evaluated their risk of acquiring HIV appropriately, which lead the authors to recommend PrEP for everyone perceiving themselves at risk, resulting in broader eligibility criteria [54]. The high contextuality and fluctuation of sexual (risk) behavior over time [55] justifies positioning PrEP as a positive sexual health promotion and wellness framing tool potentially avoiding PrEP-related stigma [56]. In addition, such branding and roll-out would avoid the ethical dilemma arising when denying someone PrEP coming forward for this prevention tool because of currently insufficient ‘risk behavior’ [57].…”
Section: Discussioncontrasting
confidence: 89%
“…In contrast to our findings, it was recently observed that MSM in England self-evaluated their risk of acquiring HIV appropriately, which lead the authors to recommend PrEP for everyone perceiving themselves at risk, resulting in broader eligibility criteria [54]. The high contextuality and fluctuation of sexual (risk) behavior over time [55] justifies positioning PrEP as a positive sexual health promotion and wellness framing tool potentially avoiding PrEP-related stigma [56]. In addition, such branding and roll-out would avoid the ethical dilemma arising when denying someone PrEP coming forward for this prevention tool because of currently insufficient ‘risk behavior’ [57].…”
Section: Discussioncontrasting
confidence: 89%
“…Further, most of the previous studies exploring functionality of apps for HIV prevention among MSM mainly focused on behavioral changes and paid less attention to psychosocial aspects. The behavioral and psychosocial conditions of MSM are interrelated, the co-occurrence of multiple psychosocial problems, such as depressive conditions and discrimination, could interact to generate additive effects on HIV-related sexual risk behaviors and HIV incidence [ 22 24 ]. Thus, HIV prevention interventions should be developed under an integrated framework, combine behavioral with psychosocial aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the lowest mean age (20 years old) was related to the three studies of Bruce et al, Holloway. et al and Kipke et al [ 27 , 41 , 44 ] while the highest mean age (57 years old) was related to the study of Zepf et al [ 86 ]. Also, the overall mean age in the meta-analysis was 32 years.…”
Section: Resultsmentioning
confidence: 96%
“…In the present meta-analysis, the first study to report the prevalence of depression in MSM was the article of Mills et al [ 55 ], and the most recent study which measured the prevalence of depression in MSM was the article of Clark et al [ 32 ]. The highest number of studies was related to 2018 with 14 articles [ 26 , 31 , 34 , 46 , 47 , 50 , 58 , 60 , 62 , 69 , 71 , 77 , 84 , 89 ] and 2017 with 11 articles [ 28 , 30 , 38 , 40 , 41 , 43 , 54 , 56 , 67 , 70 , 73 ]. The smallest sample size was related to the study of Armstrong et al [ 25 ] with 56 people, and the highest was related to the study of Tomori et al [ 71 ] with 11,771 people.…”
Section: Resultsmentioning
confidence: 99%